FK506-Binding Protein 13 Expression Is Upregulated in Interstitial Lung Disease and Correlated with Clinical Severity. A Potentially Protective Role - Tat, Victor; Ayaub, Ehab A.; Ayoub, Anmar; Vierhout, Megan; Naiel, Safaa; Padwal, Manreet K.; Abed, Soumeya; Mekhael, Olivia; Tandon, Karun; Revill, Spencer D.; Yousof, Tamana; Bellaye, Pierre-Simon; et al. (American journal of respiratory cell and molecular biology, 2021)
Pulmonary fibrosis is a progressive lung disease characterized by myofibroblast accumulation and excessive extracellular matrix deposition. We sought to investigate the role of FKBP13 (13-kD FK506-binding protein), an endoplasmic reticulum-resident molecular chaperone, in various forms of pulmonary fibrosis. We first characterized the gene and protein expression of FKBP13 in lung biopsy specimens from 24 patients with idiopathic pulmonary fibrosis and 17 control subjects. FKBP13 expression was found to be elevated in the fibrotic regions of idiopathic pulmonary fibrosis lung tissues and correlated with declining forced vital capacity and dyspnea severity. FKBP13 expression was also increased in lung biopsy specimens of patients with hypersensitivity pneumonitis, rheumatoid arthritis, and sarcoidosis-associated interstitial lung disease. We next evaluated the role of this protein using FKBP13 mice in a bleomycin model of pulmonary fibrosis. Animals were assessed for lung function and histopathology at different stages of lung injury including the inflammatory (Day 7), fibrotic (Day 21), and resolution (Day 50) phases. FKBP13 mice showed increased infiltration of inflammatory cells and cytokines at Day 7, increased lung elastance and fibrosis at Day 21, and impaired resolution of fibrosis at Day 50. These changes were associated with an increased number of cells that stained positive for TUNEL and cleaved caspase 3 in the FKBP13 lungs, indicating a heightened cellular sensitivity to bleomycin. Our findings suggest that FKBP13 is a potential biomarker for severity of interstitial lung diseases and that it has a biologically relevant role in protecting mice against bleomycin-induced injury, inflammation, and fibrosis.